Anti-proliferative effects of recombinant iron superoxide dismutase on HepG2 cells via a redox-dependent PI3k/Akt pathway - Lu, Min; Bi, Chong-shan; Gong, Xing-guo; Chen, Han-min; Sheng, Xie-huang; Deng, Tong-le; Xu, Ke-di (Applied microbiology and biotechnology, 2007)
The coding sequence for an iron superoxide dismutase (fe-sod) was amplified from the Nostoc commune genome. Recombinant Fe-SOD was overexpressed in Escherichia coli, accounting for ~76% of total bacterial protein. Fe-SOD was purified from bacterial lysate by Ni-NTA column chromatography and used to generate an anti-SOD antibody. The purified Fe-SOD was encapsulated in liposomes and delivered to HepG2 liver tumor cells to eliminate cellular superoxide anions. The SOD-loaded cells exhibited lower reactive oxygen species (ROS) levels and higher reduced glutathione (GSH) levels. In Fe-SOD-treated cells, the cell cycle was delayed in the G₁ phase, and HepG2 cell growth slowed in association with dephosphorylation of the serine-threonine kinase Akt. Low-dose H₂O₂ stimulated Akt phosphorylation, implying that Akt activation in HepG2 cells is redox-sensitive. Akt phosphorylation was abrogated by phosphatidylinositol 3-kinase (PI3K) inhibitors, suggesting that PI3K is an upstream mediator of Akt activation in HepG2 cells. This study provides insight into recombinant Fe-SOD-induced signaling mechanisms in liver tumor cells and suggests the feasibility of using Fe-SOD as an antitumor agent.